Young People's Political Participation: New and Old Forms in Contemporary Spain - Francisco Javier Alarcón González (Coordinamento SIBA, 2021)
This article is related to the literature concerning the decline of traditional forms of political participation in young people. It seeks to understand younger Spaniards' attitudes towards active participation in democratic processes and, more specifically, differences between those young people engaged in citizen-oriented political actions related to political parties and those engaged in cause-oriented activities. The main goal of this paper is to explain the relationship between young people and politics, focusing on three types of comparisons: (i) between young people, adults and seniors, (ii) in both kinds of actions, and (iii) across three theoretical models that scholars have been used indiscriminately to testing different models explaining why people became active in politics, each of them influenced by different political science research traditions. Data show a great disparity in the explanatory power of independent variables among age groups. A better performance of civic volutantism model and also in cause-oriented participation.